Metabolomics on Integrated Circuit. (2017) - Cheah, Boon Chong; MacDonald, Alasdair I.; Barrett, Michael P.; Cumming, David R.S.
Abstract: We have demonstrated a chip-based diagnostics tool for the quantification of metabolites, using specific enzymes, to study enzyme kinetics and calculate the Michaelis-Menten constant. An array of 256×256 ion-sensitive field effect transistors (ISFETs) fabricated in a complementary metal oxide semiconductor (CMOS) process is used for this prototype. We have used hexokinase enzyme reaction on the ISFET CMOS chip with glucose concentration in the physiological range of 0.05 mM – 231 mM and successfully studied the enzyme kinetics of hexokinase in detail. This will promote future research towards multiplexing enzyme-based metabolite quantification on a single chip, ultimately opening a pathway towards a personal metabolome machine.